Implementation of coordination tests on the physical condition of early age badminton players - Agus Wiyanto; Muh. Isna Nurdin Wibisana; Masri Masri; Karimuddin Karimuddin; Novi Lidya Isdarianti; Zulfikar Zulfikar (Sriwijaya Journal of Sport, 2024)
Coordination for young badminton players is very important so tests and measurements need to be carried out to determine the skills they have achieved. The aim of the research is to find out the results of tests and measurements of the coordination of early childhood badminton players. Quantitative methods through tests and measurements are carried out. Respondents were determined using purposive sampling involving 30 young male badminton players and 10 female badminton players using tests and measurements. Descriptive percentage data analysis techniques were applied. The research procedure applies a coordination test by hitting a wall at 2 meters for 60 second. The test results for male badminton players at the early age category are very good = 2, good = 3, moderate = 8, poor = 7 and very poor = 10. For female badminton players at an early age, very good = 1, good = 1, moderate = 2, poor = 1 and very less = 5. Research findings show that not all young badminton players have good coordination test results, so there needs to be proper evaluation by the coach regarding the training program to get optimal results. In conclusion, the coordination test can be used as a snapshot of the progress of training development so that it can accurately measure the abilities of early childhood badminton players and can also be used as a track record of the badminton player which can be used as a guide and follow-up actions can be taken to improve the player's movement skills.